Family Expectations: Forcing Korea's LGBT Community into the Closet - HEARNE DANIELLE NICOLE (Graduate School of International Studies Ajou University, 2015)
This paper seeks to explore the relationship between staying in the closet and familial pressures, such as marriage and children, in Korean society. Korea’s LGBT community has faced many challenges over the past few decades and, while acceptance of same-sex relationships is higher than ever, many same-sex couples are still finding it difficult to face their families and admit their sexual orientation. Previous studies regarding homosexuality in Korea have been lacking and illustrate the insufficient amount of support that Korea’s LGBT community receives. Some of the biggest obstacles for same-sex rights in Korea come from religious groups lobbying the government to listen to only their perspective, as well as the lack of exposure in Korean society in general. This paper will propose a study that aims to identify why LGBT individuals in Korea choose to stay in the closet and allow their voices to be ignored.
학위논문(석사)--아주대학교 Graduate School of International Studies :NGO학과,2015. 2
Keywords: Family